Análise das incidências de manifestações patológicas oriundas do recalque de fundações: estudo de caso na UFERSA-Angicos - Fernandes, Larissa Hellen Alves (Universidade Federal Rural do Semi-Árido, 2020)
Civil construction is an area that has been expanding over time due to population development, linked to technological advancement. However, despite the use of new technologies in the construction field, in construction processes and materials, a significant index of pathological manifestations of the most varied species has been identified in buildings. Pathological manifestations can occur in the most varied ways and in the different elements that make up the buildings. Foundations are structural elements responsible for transmitting building loads to the ground, and when poorly executed, they reflect on other elements such as masonry in the form of cracks, cracks and other damage. These problems may arise due to the negligence in the stages of characterizing the soil behavior and investigation, analysis and design of the foundations, execution of the foundations. Thus, the present work presents a study on the incidence of pathological manifestations arising from the poor execution of the foundations of some blocks of the Federal Rural University of the Semi-Arid - Campus Angicos. With the study carried out, it was found cracks inclined at 45º, characteristics in which the cracks caused by repression present.
Artigo
Keywords: Patologia; Fundação; Recalque; Pathology; Foundation; Repression; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA